Optogenetic control of nuclear protein export - Niopek, Dominik; Wehler, Pierre; Rönsch, Julia; Eils, Roland; Di Ventura, Barbara (Nature Communications, 2016)
Active nucleocytoplasmic transport is a key mechanism underlying protein regulation in eukaryotes. While nuclear protein import can be controlled in space and time with a portfolio of optogenetic tools, protein export has not been tackled so far. Here we present a light-inducible nuclear export system (LEXY) based on a single, genetically encoded tag, which enables precise spatiotemporal control over the export of tagged proteins. A constitutively nuclear, chromatin-anchored LEXY variant expands the method towards light inhibition of endogenous protein export by sequestering cellular CRM1 receptors. We showcase the utility of LEXY for cell biology applications by regulating a synthetic repressor as well as human p53 transcriptional activity with light. LEXY is a powerful addition to the optogenetic toolbox, allowing various novel applications in synthetic and cell biology.
Gesehen am 03.11.2020